Measuring Severity of Downtime Influence Factors to Naval Ship Operational Availability: A Delphi Study - Bin Abdul Wahid, Al-Shafiq; Zamani Bin Ahmad, Mohd; ., Sunarsih; Najib Bin Abdul Ghani Yolhamid, Mohd; Abu Ubaidah Amir Abu Zarim, Mohamad; Binti Abdullah, Aisha; Hanani Bt Ahmad Azlan, Nur (International Journal of Engineering and Technology, 2018)
Rapid development of shipbuilding and ship repair industry in recent years has been increasingly transforming the way organizations apply the long term strategic thinking of â€œcradle to graveâ€ maintenance approach in order to maximize their growth in a dynamic marine industry. With increased ship complexity, size and revolutionary design, organizations strive to balance ideal maintenance philosophies against on-going efforts of cost reduction whilst maintaining high availability of vessels. Despite aspiration and efforts to improve the ship availability, the Royal Malaysian Navy [RMN] vessels which are currently maintained under the In Service Support [ISS] Contracts are hardly tackling the human and equipment related aspects due to limited knowledge and available data on ship Downtime Influence Factors [DIFs]. The current research carried out an explorative study across various engineering disciplines to generate RMN ship maintenance DIFs and their severity measures via a 3-Stage Modified Delphi approach. 30 Experts experienced in daily implementation of naval ship maintenance contracts were involved. In the first stage, Focus Group Discussions [FGDs] amongst Experts were conducted to produce the DIFs, followed by questionnaire distribution to measure the severity of the DIFs in the second stage. In the third stage, the Severe DIFs were confirmed and ranked based on a Risk Assessment method. The study revealed 50 DIFs to RMN ship availability and deduced the top 15 Severe DIFs pinpointing the key problem areas to prioritize efforts in improving RMN ship availability.Â Â